The influence of audit committee and auditors type on risk disclosure in UK - chen, meixintian (2017)
This dissertation examines how audit committee characteristics and auditor types can affect the quality of risk disclosure in the annual reports of 70 non-financial firms in the UK during the period from 2015 to 2016. : The current findings support that audit committees in UK firms have a significant impact on risk disclosure quality. This study finds that audit committee (hereafte AC) independence facilitates listed firms to disclose risks with greater quality. The findings also show that AC members who have varied knowledge in professional fields contribute to improving the quality of risk disclosure. Furthermore, this study’s findings report that an AC consisting of more directors motivates firms to provide more risk information with higher quality. The results also imply that the more frequent meeting of AC members helps firms in the UK enhance their risk disclosur (hereafte RD) quality while releasing more information about risk solutions. Furthermore, this dissertation unexpectedly finds that if AC directors hold other positions in different firms, it will make the quality of RD deteriorate as their time is split between companies. Moreover, the findings present that the positive influence of AC characteristics is stronger when auditors are the Big Four firms. According to the current findings, it seems that auditor type does not affect the quality of RD at a significant level.This dissertation emphasises the monitoring role of audit committees when examining the quality of risk disclosure. The findings confirm the positive effects of AC characteristics on RD quality and, additionally, provide new findings of the negative effect of directors on risk disclosure. The empirical findings of this dissertation suggest that the RD quality can be improved by increasing the size of the AC, more frequent meetings, knowledgeable directors and an independent AC. These improvements can leads to increased market efficiency by reducing agency costs and information asymmetry.